Letter from Max Bredig to Ernst A. Hauser, February 24, 1946 - Bredig, Max Albert (1946)
Max Bredig (1902-1977) defends his written opinion in his latest letter to the editor, in which he responded to an article by Ernst A. Hauser (1896-1956). In this article, Hauser praised Wolfgang Ostwald (1883-1943) for his successful research on colloids. Wolfgang Ostwald, the son of the renowned chemist, Wilhelm Ostwald (1853-1932), became a full professor of chemistry at the University of Leipzig in 1935. In his letter to the editor, Max Bredig points out that anyone hired or promoted as a professor at the University of Leipzig at this time was considered to be closely connected to the Nazi party. Bredig doubles down on his denouncement of Ostwald, calling Ostwald and all other sympathizers "criminal fools," complicit in the ultimate murder of many of Bredig's Jewish colleagues.
Keywords: Bredig, Max Albert, 1902-1977; Hauser, Ernst A. (Ernst Alfred), 1896-1956; Ostwald, Wolfgang, 1883-1943; Jewish Holocaust (1939-1945); National socialism